Diagnostic Accuracy of Tissue Impedance Measurement Interpretation for Correct Veress Needle Placement in Feline Cadavers1. Issue 5 (1st February 2013) - Hyink, Sara; Whittemore, Jacqueline C.; Mitchell, Amanda; Reed, Ann
Abstract: Objective: To determine the diagnostic accuracy of tissue impedance measurement interpretation (TIMI) for determining correct versus incorrect Veress needle placement in feline cadavers. Study Design: Prospective, randomized, blinded trial. Study Population: Cat cadavers (n = 24). Methods: Two laparoscopists (1 experienced, 1 novice), blinded to TIMI, placed reusable Veress needles in study subjects in a randomized order. A third individual interpreted impedance measurements as consistent with correct versus incorrect placement. Veress needle tip locations were marked by injecting contrasting colors of India ink. Tissue dissection was performed to localize ink. Sensitivity, specificity, accuracy, precision, and kappa statistics for TIMI for placements by the experienced and novice laparoscopist were determined. P < .05 was considered significant. Results: TIMI identified 36/38 correct and 2/10 incorrect placements. TIMI identified 2/2 bowel perforations but was unable to identify 8 inappropriate placements in the retroperitoneal fat pad. Impedance measurement interpretation had 94.7% sensitivity, 20% specificity, 79.2% accuracy, and 81% precision overall. Agreement between TIMI and Veress needle location was absent (kappa = −0.15, P = .01) for placements by the experienced laparoscopist and substantial (kappa = 0.78, P < .01) for the novice laparoscopist. Conclusions: Failure of TIMI to identify placement in the retroperitoneal fat pad resulted in poor accuracy. Small cat size limited the number of appropriate placement sites, perhaps resulting in excessively dorsal placements. Use of TIMI may increase detection of clinically significant inappropriate Veress needle placements, like bowel perforations, and decrease installment phase complications. Further evaluation of Veress needle placement with and without TIMI is warranted.